Mechanisms of checkpoint inhibition-induced adverse events. (21st February 2020) - Urwyler, P; Earnshaw, I; Bermudez, M; Perucha, E; Wu, W; Ryan, S; Mcdonald, L; Karagiannis, S N; Taams, L S; Powell, N; Cope, A; Papa, S
Summary: Immune checkpoint inhibition has revolutionized the treatment of several solid cancers, most notably melanoma and non-small-cell lung cancer (NSCLC). Drugs targeting cytotoxic T lymphocyte antigen (CTLA)-4 and programmed cell death 1 (PD-1) have made their way into routine clinical use; however, this has not been without difficulties. Stimulation of the immune system to target cancer has been found to result in a reduction of self-tolerance, leading to the development of adverse effects that resemble autoimmunity. These adverse effects are erratic in their onset and severity and can theoretically affect any organ type. Several mechanisms for immune-related toxicity have been investigated over recent years; however, no consensus on the cause or prediction of toxicity has been reached. This review seeks to examine reported evidence for possible mechanisms of toxicity, methods for prediction of those at risk and a discussion of future prospects within the field. Graphical Abstract: